2021
DOI: 10.1038/s42003-021-02697-8
|View full text |Cite
|
Sign up to set email alerts
|

Taxus yunnanensis genome offers insights into gymnosperm phylogeny and taxol production

Abstract: Taxol, a natural product derived from Taxus, is one of the most effective natural anticancer drugs and the biosynthetic pathway of Taxol is the basis of heterologous bio-production. Here, we report a high-quality genome assembly and annotation of Taxus yunnanensis based on 10.7 Gb sequences assembled into 12 chromosomes with contig N50 and scaffold N50 of 2.89 Mb and 966.80 Mb, respectively. Phylogenomic analyses show that T. yunnanensis is most closely related to Sequoiadendron giganteum among the sampled tax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…This unique set of characters has led many people to believe that the gnetophytes are direct ancestors (pseudanthial hypothesis) or relatives of ancestors of the angiosperms (anthophyte and euanthial hypotheses) ( Yang et al., 2004 ; Friis et al., 2011 ). However, molecular phylogenetic studies have indicated that gnetophytes constitute a monophyletic group that is either sister to the Pinaceae (gnepine hypothesis, Gugerli et al., 2001 ; Ran et al., 2018a ; Stull et al., 2021 ; Liu et al., 2022 ), or to the Cupressophytes, including Sciadopityaceae, Cupressaceae and Taxaceae (gnecup hypothesis, Wu et al., 2013 ), or to the conifers (gnetifer hypothesis, Ran et al., 2010 ), or to other living gymnosperms ( Wang and Ran, 2014 ), or to other living seed plants ( Wang and Ran, 2014 ; Song et al., 2021 ; Niu et al., 2022 ). Nuclear genomes of Gnetaceae and Welwitschiaceae were published recently ( Wan et al., 2018 , 2021 ).…”
Section: Recent Advancesmentioning
confidence: 99%
“…This unique set of characters has led many people to believe that the gnetophytes are direct ancestors (pseudanthial hypothesis) or relatives of ancestors of the angiosperms (anthophyte and euanthial hypotheses) ( Yang et al., 2004 ; Friis et al., 2011 ). However, molecular phylogenetic studies have indicated that gnetophytes constitute a monophyletic group that is either sister to the Pinaceae (gnepine hypothesis, Gugerli et al., 2001 ; Ran et al., 2018a ; Stull et al., 2021 ; Liu et al., 2022 ), or to the Cupressophytes, including Sciadopityaceae, Cupressaceae and Taxaceae (gnecup hypothesis, Wu et al., 2013 ), or to the conifers (gnetifer hypothesis, Ran et al., 2010 ), or to other living gymnosperms ( Wang and Ran, 2014 ), or to other living seed plants ( Wang and Ran, 2014 ; Song et al., 2021 ; Niu et al., 2022 ). Nuclear genomes of Gnetaceae and Welwitschiaceae were published recently ( Wan et al., 2018 , 2021 ).…”
Section: Recent Advancesmentioning
confidence: 99%
“…5C), 76 and taxol biosynthesis in Taxus spp., of the Coniferophyte lineage. 51,77 The lack of described examples outside angiosperms is not likely due to a real scarcity of BGCs in these lineages but rather due to the paucity of genome sequences, a result of genome complexity and investigation bias. As new genomes in these lineages are sequenced, more BGCs will be discovered.…”
Section: Taxonomic Distributionmentioning
confidence: 99%
“…The genomes of 2 iconic species from the Cupressaceae family, the giant sequoia ( Sequoiadendron giganteum , 8.1 Gb) and the coast redwood ( Sequoia sempervirens , a hexaploid genome of 26.5 Gb), were successively decoded with conspicuously enhanced contiguity [ 6 , 38 ]. Additionally, 3 assembly data resources for a single genus, Taxus , were released almost simultaneously, reflecting the great interest in the gymnosperm genomes [ 22 , 39 , 40 ]. Notably, all the records provided impressively complete genomes, as suggested by assembly lengths (contig N50 = 2.44 Mb in Taxus chinensis , 2.89 Mb in Taxus yunnanensis , and 8.60 Mb in Taxus wallichiana ) and the coverage of the core Embryophyta gene library [ 41 ] (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the various ages estimated by different studies of the LTR outbreaks of the same gymnosperm could be partially explained by the different neutral mutation rates assigned (i.e., 7.3 × 10 −10 was used for T. yunnanensis and T. chinensis var. mairei [ 22 , 40 ]). It is worth mentioning that the outlier Welwitschia has suffered from a very recent expansion of both autonomous and nonautonomous LTRs in less than 1 to 2 Ma, which probably resulted from a cascade of events triggered by intense aridity [ 27 ].…”
Section: Introductionmentioning
confidence: 99%